Anatomical variation of the palmaris longus muscle: finding in zone V flexor injury - A. Azcue, Arsenio F.; Gómez, Bryan M. (International Journal of Research in Medical Sciences, 2023)
The palmaris longus is a muscle located on the anterior surface of the forearm, known for its significant anatomical variability. This ranges from its absence, the most common variant, to having multiple insertions or muscular bellies. The aim of the study is to highlight the uncommon anatomical variant diagnosed as an incidental finding and to contribute to the statistics of this type of pathology in our country. A case is reported involving a 14-year-old patient with no significant medical history who sustained a cut injury. Surgical exploration through the previous wound was conducted by the plastic surgery department at the General Hospital of Mexico (2023). The incidental finding revealed complete laceration of both tendons of the palmaris longus muscle, prompting the repair of both tendons. The bifid palmaris longus is a rare anatomical anomaly, not previously described in the statistics of our country. Therefore, the significance of reporting this anatomical variant as an incidental finding is noteworthy.